Origin of Sedimentary BHPs Along a Mississippi River–Gulf of Mexico Export Transect: Insights From Spatial and Density Distributions - Kusch, Stephanie; Sepúlveda, Julio; Wakeham, Stuart G. (Frontiers in Marine Science, 2019)
We investigated the origin of sedimentary bacteriohopanepolyols (BHPs) in low-density (<1.6 g cm−3), mesodensity (1.6-2.0 g cm−3 and 2.0-2.5 g cm−3) and high-density fractions (>2.5 g cm−3) as well as unfractionated bulk samples in a highly dynamic coastal setting along a transect spanning from the Mississippi Delta into the Gulf of Mexico. We observe selective partitioning of BHPs among density fractions both in total abundance and structural diversity. BHPs primarily accumulate in the low-density fraction at all sites. Good correlation with other particle properties (surface area-normalized organic carbon loadings [OC/SA], C/N ratios, Δ14C values, and lignin phenol abundances) and the spatial distribution of absolute and relative BHP abundances suggests that a significant fraction of BHPs are terrestrially sourced and entrained in the OC pool that is stabilized on clay particles or associated with plant fragments. Only a small subset of BHPs seems to have a significant autochthonous origin at the station furthest offshore and they are associated with the low and mesodensity fractions. While provenance and hydrodynamic sorting of particles across the shelf seem to primarily determine BHP inventories along the transect, the samples also harbor an unusual diversity of amino-functionalized BHPs. A subset of these BHPs appears to derive from aerobic methane oxidizing bacteria and are likely exported with particles from the coastal swamps in the Mississippi Delta. Other amino-functionalized BHPs seem to derive from aerobic ammonia oxidizing bacteria thriving in the nutrient-rich Mississippi River plume. We find no evidence for anaerobic ammonium oxidizing bacteria related to recurring seasonal hypoxia on the Louisiana Shelf.